2020
DOI: 10.1088/2053-1591/ab7d0d
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and precipitation behavior of the 0.1C-18Cr-1Al-1Si ferritic heat-resistant stainless steel during hot deformation

Abstract: The 0.1C-18Cr-1Al-1Si ferritic heat-resistant stainless steel has attracted considerable attention to high-temperature applications due to its favorable combination of creep and oxidation resistance. In this paper, the microstructural evolution and precipitation behavior of the 0.1C-18Cr-1Al-1Si ferritic heat-resistant stainless steel is studied from the compression deformation data in the temperature range of 850°C-1050°C and the strain rate range of 0.01-1 s −1 . Experimental results demonstrate that higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Moreover, energy dispersive spectroscopy results indicated that the precipitates were composed of ferrum, chromium, carbon and silicon. Combined with the above-mentioned analysis and the previous literature information, it could be deduced that the fine precipitates were most likely the ðCr; FeÞ 23 C 6 [19]. The precipitates in the sample batch annealed at 850 °C for 10 hours and then cold-rolled annealed at 900 °C were analyzed with energy dispersive spectroscopy, Figure 7.…”
Section: Microstructure Analysismentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, energy dispersive spectroscopy results indicated that the precipitates were composed of ferrum, chromium, carbon and silicon. Combined with the above-mentioned analysis and the previous literature information, it could be deduced that the fine precipitates were most likely the ðCr; FeÞ 23 C 6 [19]. The precipitates in the sample batch annealed at 850 °C for 10 hours and then cold-rolled annealed at 900 °C were analyzed with energy dispersive spectroscopy, Figure 7.…”
Section: Microstructure Analysismentioning
confidence: 83%
“…For samples annealed for 10 hours at 700 °C, 750 °C and 800 °C, the deformed microstructures were al-most identical with that from the hot-rolled sheet (not recrystallized), Figure 2b-d. That is because the softening mechanism at a lower temperature was mainly the dynamic recovery and low annealing temperature could not result in significant structural changes associated with recrystallization [19]. When increasing the annealing temperature to 850 °C, it was found that the microstructures were partially recrystallized, a few recrystallization nuclei and new grains were discerned, but a large number of elongated/deformed grains still presented along the rolling direction.…”
Section: Microstructure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The reason may be due either to machine compliance or to a high rate of data acquisition. 26) 3.2 Microstructure evolution and precipitation behavior Figure 3 shows the microstructure before hot deformation. It can be seen that the distribution of ferrite grains are relatively uniform and the average grain size is 127.3 µm.…”
Section: The Flow Behavior During Tot Deformationmentioning
confidence: 99%
“…Precipitation pinning on the boundary retards recrystallization. Zhang et al [7] found that Cr23C6 on the boundary effectively prevents DRX during the high temperature deformation process of 0.1C-18Cr-1Al-1Si ferritic stainless steel. In a study by Liu et al [8] on 19Cr2Mo ferritic stainless steel, the addition of W reduced the size of the Laves phase and increased the amount of precipitation, and the smaller and more precipitation on the boundary effectively prevented DRX.…”
Section: Introductionmentioning
confidence: 99%